Surface- and substrate-coated catalytic membrane for mitigating interference of water matrix species in intensified micropollutant confinement oxidation - Liangdy, Arvin (2025)
The integration of advanced oxidation processes (AOPs) with membrane technology offers benefits for catalyst recovery and reducing membrane fouling. However, the application of the hybrid process could be hampered by the background species in water matrix. This study addresses this challenge by developing catalytic ceramic membranes (CCMs) with dual mechanisms to intensify acetaminophen (ACT) removal in water. The CCMs effectively activated peroxymonosulfate (PMS), achieving ACT degradation of 85 % and 93 % in real water matrices (reverse osmosis retentate and settled water, respectively) and 99 % in MQ water. The CCMs demonstrated consistent performance across multiple operational cycles, even in the presence of humic acid (HA) (96 % ACT reduction). The CCM design features Co3O4 catalytic layer on CCM surface, facilitating surface oxidation, reducing fouling, and TiO2 intermediate rejection layers serving as barrier for bulk organic pollutants, achieving 50 % HA removal through rejection and 70 % with 1.5 mM PMS. This design facilitates catalytic degradation at the membrane surface, allowing retention and degradation of bulk organic pollutants and intermediates, while ACT permeates into CCM substrate. The surface oxidation and rejection enhanced confinement oxidation within the Co3O4-coated macropores, minimizing interference from background species. LC-QTOF analysis identified multiple degradation pathways, including hydroxylation, acetyl-amino group cleavage, side chain oxidation and benzene ring cleavage, with intermediates showing reduced toxicity. Reactive oxygen species involved in the system were identified and PMS activation mechanism was proposed. This research highlights the potential of the hybrid process, enhancing micropollutant removal by mitigating interference from background species, providing practical implications in water treatment applications.